The Effect of Live Streaming and Free Shipping on Tiktok Shop’s Purchase Decisions Moderated by Discounts Price - Novitasari Novitasari; Lentina Wati Simarmata (Journal Of Marketing and Technology Management, 2025)
This study aims to analyze the influence of live streaming and free shipping on fashion product purchase decisions on Tiktok Shop, as well as test the role of discounts as moderation. Tiktok Shop has become an interesting platform to research because of its rapidly increasing popularity in fashion product sales. The quantitative method is used by distributing questionnaires to consumers who have purchased fashion products on the Tiktok Shop. The sample in this study was 170 respondents. The analysis tool used is moderation analysis using the SmartPLS 4.0 tool. The conclusion of the study shows that live streaming and free shipping on Tiktok Shop significantly affect consumer purchase decisions. However, discounts as a moderation variable do not play a role in strengthening or weakening the influence of live streaming and free shipping on purchase decisions. In other words, although discounts are an important factor in purchasing decisions in general, their existence does not change the effectiveness of live streaming and free shipping in influencing consumers on TikTok Shop.